Apoyo social y malestar psicológico en diferentes grupos de edad de adultos argentinos - Aceiro, María Agustina; Delfino, Gisela; González Insua, Francisco; Grasso, Lina; Rodríguez Espínola, Solange (Pontificia Universidad Católica del Perú, 2025)
Psychological distress (PD) involves a deficit in emotional capacities. Social support (SS), structural and functional, is a protective factor for health as it reduces stress and distress. Previous literature indicates that both variables are related and vary throughout adulthood. Based on a cross-sectional study (n=5388; 53.7% women; age: 18-98, M=43.15; SD=17.38), we aimed to analyze whether age is a moderating factor in the relationship between SS and PD in adulthood. A deficit in SS is related to PD, and age moderates between them. The relationship between PD and structural SS is more potent in older adults, while instrumental and informational SS is more robust in younger adults. Affective SS is the best predictor of PD regardless of age.

El malestar psicológico (MP) implica un déficit en capacidades emocionales. El apoyo social (AS), estructural y funcional, es un factor protector para la salud, ya que reduce el estrés y el malestar. La literatura indica que ambas variables están relacionadas y varían en la adultez.Basándonos en un estudio transversal (n=5388; 53,7% mujeres; edad: 18-98, M=43,15; SD=17,38), analizamos si la edad modera la relación entre AS y MP. Un déficit en AS se relaciona con MP, y la edad modera esta relación. La relación entre MP y AS estructural es más fuerte en adultos mayores, mientras que el AS instrumental e informacional es más robusto en jóvenes. El AS afectivo es el mejor predictor de MP, independientemente de la edad.
Social support and psychological distress across different age groups in Argentine adults
Keywords: Mental health; Depression; Anxiety; Social network; Age moderation; Salud mental; Depresión; Ansiedad; Red social; Moderación por edad; Saúde Mental; Depressão; Ansiedade; Redes Sociais; Moderação de Idade; https://purl.org/pe-repo/ocde/ford#5.01.00